DEFENSORIA PÚBLICA E PRECEDENTES: um estudo de caso sobre a Defensoria Pública do Maranhão dentro do sistema de precedentes - LIMA, Luciana dos Santos (2024)
The evolution of social man brings with it a restlessness that reflects the search for the recognition of fundamental rights for the development of a dignified life. In this effort, guarantees such as access to justice stand out with the purpose of ensuring the realization of the rights protected by the 1988 Constitution. Furthermore, in the specific field of defending the interests of the vulnerable population, the Public Defender's Office gains strength, which is now recognized as a permanent institution essential to the jurisdictional function of the State. As a continuous act, with the aim of giving new meaning to judicial activity, the 2015 Code of Civil Procedure came into being, which now provides for judicial precedents as a way of emphasizing the concern with a coherent and stable stance of agents inserted in the justice system. It is within this context that the research is carried out, which consists of a case study that, using as a reference the Committee of Qualified Precedents of the Public Defender's Office of São Paulo, analyzes the reality of the Public Defender's Office of Maranhão within the system brought by judicial precedents.